2013
DOI: 10.1038/ncomms3722
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into dGTP-dependent activation of tetrameric SAMHD1 deoxynucleoside triphosphate triphosphohydrolase

Abstract: SAMHD1 is a dGTP-activated deoxynucleoside triphosphate triphosphohydrolase (dNTPase) whose dNTPase activity has been linked to HIV/SIV restriction. The mechanism of its dGTPactivated dNTPase function remains unclear. Recent data also indicate that SAMHD1 regulates retrotransposition of LINE-1 elements. Here we report the 1.8-Å crystal structure of homotetrameric SAMHD1 in complex with the allosteric activator and substrate dGTP/dATP. The structure indicates the mechanism of dGTP-dependent tetramer formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
178
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(189 citation statements)
references
References 48 publications
10
178
1
Order By: Relevance
“…30 Zhu et al also found that dGTP-triggered tetramer formation of SAMHD1 is important for dNTP depletion and SAMHD1-mediated inhibition of LINE-1 transposition. 35 Results from our group confirmed the restriction of LINE-1 by SAMHD1 and also suggested an alternative mechanism of action. 29 The first key observation of our study is that SAMHD1 expression enhances the localization of LINE-1 RNP into cytoplasmic stress granules.…”
supporting
confidence: 74%
“…30 Zhu et al also found that dGTP-triggered tetramer formation of SAMHD1 is important for dNTP depletion and SAMHD1-mediated inhibition of LINE-1 transposition. 35 Results from our group confirmed the restriction of LINE-1 by SAMHD1 and also suggested an alternative mechanism of action. 29 The first key observation of our study is that SAMHD1 expression enhances the localization of LINE-1 RNP into cytoplasmic stress granules.…”
supporting
confidence: 74%
“…The majority of the mutations were predicted to be deleterious by using in silico analysis: 87% were predicted to be damaging by at least one of four computational tools (Grantham, SIFT, PolyPhen2, and CADD), 72% by two or more tools, and 50% by three tools (Table S1) (37)(38)(39)(40). Four of the mutations (R145, D207, R366, and R451) are located at amino acid residues that have been reported to have functional significance in in vitro studies (27,41,42).…”
Section: Samhd1mentioning
confidence: 99%
“…Unlike GTP, dGTP can activate its own hydrolysis and is known to serve as a transactivator for hydrolysis of other substrate dNTPs at low concentrations (17). However, it should also act as an inhibitor of dNTP hydrolysis at higher concentrations (20,22). To explore these properties of dGTP, we determined the concentration dependence of the initial rates of dGTP hydrolysis at an SAMHD1 concentration of 0.2 μM and variable concentrations of dGTP in the range of 5 μM to 5 mM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structural basis for the increased dimer affinity apparently results from docking of the guanine base of GTP into the highly specific guanine binding site on one monomer and the formation of electrostatic interactions between its triphosphate group and the second monomer of the dimer (Fig. S9 A and B) (22). Hence, GTP serves as a nucleotide tether to bring together monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation